Pengendalian Persediaan Bahan Baku Kedelai dengan Menggunakan Metode Economic Order Quantity (EOQ) pada UKM Tempe Sari Jaya - Rizki Rifaldi; Candra Pratama; Naufan Alamsyah; Budiharjo Budiharjo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Inventory control of raw materials plays an important role in maintaining production continuity and cost efficiency at UKM Tempe Sari Jaya. So far, the procurement of soybean raw materials has been based on estimation, resulting in a relatively high purchasing frequency and potentially increasing inventory costs. This study aims to determine the optimal order quantity of raw materials, purchasing frequency, safety stock, reorder point, and Total Inventory Cost using the Economic Order Quantity (EOQ) method. The research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the annual demand for soybean raw materials is 6,590 kg. Based on EOQ calculations, the optimal order quantity is 565 kg with a purchasing frequency of 12 times per year, a safety stock of 46 kg, and a reorder point of 67.7 kg. The resulting Total Inventory Cost is lower than that under the company’s previous purchasing policy. Therefore, the implementation of the EOQ method is proven to improve the efficiency of soybean raw material inventory control at UKM Tempe Sari Jaya.